2023
DOI: 10.1128/msphere.00679-22
|View full text |Cite
|
Sign up to set email alerts
|

Heat Shock Protein Inhibitors Show Synergistic Antibacterial Effects with Photodynamic Therapy on Caries-Related Streptococci In Vitro and In Vivo

Abstract: Effective therapies for the prevention and control of caries are urgently needed. Cariogenic streptococci play a key role in the occurrence and progression of caries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 65 publications
(69 reference statements)
0
3
1
Order By: Relevance
“…These results indicated that the direct effect of radiation was also a factor affecting the diversity of oral microbiota. Many studies have indicated that Streptococcus is a major contributor to caries progression because they can form biofilms and produce acid ( 23 , 24 ), while in our study, the most obvious change was the increase in Streptococcus abundance. Moreover, it is also noteworthy that in the caries-free samples, Leuconostoc significantly reduced when the radiation dose reached 80 Gy in our study.…”
Section: Discussioncontrasting
confidence: 52%
“…These results indicated that the direct effect of radiation was also a factor affecting the diversity of oral microbiota. Many studies have indicated that Streptococcus is a major contributor to caries progression because they can form biofilms and produce acid ( 23 , 24 ), while in our study, the most obvious change was the increase in Streptococcus abundance. Moreover, it is also noteworthy that in the caries-free samples, Leuconostoc significantly reduced when the radiation dose reached 80 Gy in our study.…”
Section: Discussioncontrasting
confidence: 52%
“…The data presented above demonstrated that AR extract greatly decreased the cariogenic virulence of S. mutans but did not significantly disturb the microecological balance of oral flora. In addition, in vivo experiments can also help to judge drug safety [ 62 ]. Building on previous research, the observation of hepatoprotective activity when oral arginine (AR) extracts were taken, their effects on platelet production and coagulation, as well as their capability to improve and modify liver function damage, has substantiated this claim.…”
Section: Discussionmentioning
confidence: 99%
“…Essential oils have also been shown to interfere with bacterial metabolism by interfering with protein expression in bacteria, especially some large molecular-weight proteins. 7,27 From the MiC and MBC tests, the MIC concentration of red ginger essential oil against Streptococcus mutans bacteria was 0.78% and 1.56%, and the MBC concentration was 3.125%. The results will be used for further research on the adherence test of red ginger essential oil against Streptococcus mutans bacteria using 0.78%, 1.56%, and 3.125% concentrates.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Dental caries is a condition where teeth are demineralized due to bacteria that produce acids as a result of carbohydrate fermentation and will colonize to form biofilms. 1,3,[4][5][6][7] Streptococcus mutans, a gram-positive bacterium, is identified as the primary culprit behind dental caries development in humans. Foods containing carbohydrates, especially sucrose, can accelerate the attachment of Streptococcus mutans to the enamel surface and will become dental plaque.…”
Section: Introductionmentioning
confidence: 99%